Impact of the HALP Score on Long-Term Mortality among Patients Undergoing EVAR - Mehmet Altunova; Ali Evsen; Yusuf Demir; Tuğba Aktemur; Onur Erdoğan; Sezgin Atmaca; Mehmet Köseoğlu; Nedim Uzun; Ahmet Anıl Şahin; Ömer Çelik (İstanbul Medical Journal, 2024)
Introduction: Endovascular aortic repair (EVAR) is commonly used for abdominal aortic aneurysms, but its mortality rate remains high. The hemoglobin, albumin, lymphocyte, and platelet (HALP) score, which measures hemoglobin, albumin, lymphocyte, and platelet levels, provides prognostic value by reflecting the nutritional status and systemic inflammation. This study aimed to explore the relationship between the HALP score upon admission and long-term mortality in patients with EVAR. Methods: Consecutive patients with EVAR at our tertiary center from October 2010 to August 2021 were retrospectively analyzed. HALP scores were calculated using the following formula: hemoglobin (g/L) × albumin (g/L) × lymphocyte count (/L)/platelet count (/L). In-hospital and long-term mortality data were extracted. Receiver operating characteristic curve analysis identified predictors of in-hospital mortality. Multivariate Cox regression analysis was performed to examine determinants of long-term mortality. Results: Among the 162 participants (mean age: 69.4±8.2 years, 90.1% male), the HALP score was the most significant predictor of in-hospital mortality (area under the curve: 0.752, 95% confidence interval: 0.674-0.830; p<0.001). Multivariate Cox regression analysis revealed HALP (p=0.001) and C-reactive protein (p=0.004) as independent determinants of long-term mortality. Conclusion: This study is the first to investigate the association between the HALP score and in-hospital and long-term mortality in EVAR patients. The HALP score is a robust prognostic tool compared with its components and other parameters in this patient population.